Biogenic polymer-based patches for congenital cardiac surgery: a feasibility study - Richert, Emma; Nienhaus, Andrea; Ekroll Jahren, Silje; Gazdhar, Amiq; Grab, Maximilian; Hörer, Jürgen; Carrel, Thierry; Obrist, Dominik; Heinisch, Paul Philipp (Frontiers in Cardiovascular Medicine, 2023)
Abstract Objective: Currently used patch materials in congenital-cardiac-surgery do not grow, renew or remodel. Patch calcification occurs more rapidly in paediatric patients eventually leading to reoperations. Bacterial cellulose (BC) as a biogenic-polymer offers high tensile-strength, biocompatibility and hemocompatibility. Thus, we further investigated the biomechanical properties of BC for the use as patch material. Methods: The BC-producing bacteria Acetobacter Xylinum were cultured in different environments to investigate optimal culturing conditions. For mechanical characterization, an established method of inflation for bi-axial testing was used. The applied static pressure and deflection height of the BC patch were measured. Furthermore, a displacement and strain distribution analysis was performed and compared to a standard xenograft pericardial patch. Results: The examination of the culturing conditions revealed that the BC became homogenous and stable when cultivated at 29°C, 60% oxygen concentration, and culturing medium exchange every third day for a total culturing period of 12 days. The estimated elastic modulus of the BC patches ranged from 200-530MPa compared to 230MPa for the pericardial patch. The strain distributions, calculated from preloaded (2mmHg) to 80mmHg inflation, show BC patch strains ranging between 0.6% and 4% which was comparable to the pericardial patch. However, the pressure at rupture and peak deflection height varied greatly, ranging from 67 to around 200 mmHg and 0.96 to 5.28 mm, respectively. The same patch thickness does not automatically result in the same material properties indicating that the manufacturing conditions have a significant impact on durability Conclusions: BC patches can achieve comparable results to pericardial patches in terms of strain behaviour as well as in the maximum applied pressure that can be withstood without rupture. Bacterial cellulose patches could be a promising material worth further research.